On the Ethical Issues Posed by the Exploitation of Users’ Data in MOOC Platforms: Capturing Learners’ Perspectives - Cisel, Matthieu Tenzing (International Review of Research in Open and Distributed Learning, 2023)
Due notably to the emergence of massive open online courses (MOOCs), stakeholders in online education have amassed extensive databases on learners throughout the past decade. Administrators of online course platforms, for instance, possess a broad spectrum of information about their users. This information spans from users’ areas of interest to their learning habits, all of which is deduced from diverse analytics. Such circumstances have sparked intense discussions over the ethical implications and potential risks that databases present. In this article, we delve into an analysis of a survey distributed across three MOOCs with the intention to gain a deeper understanding of learners’ viewpoints on the use of their data. We first explore the perception of features and mechanisms of recommendation systems. Subsequently, we examine the issue of data transmission to third parties, particularly potential recruiters interested in applicants’ performance records on course platforms. Our findings reveal that younger generations demonstrate less resistance towards the exploitation of their data.